Representation of Moral Value of Sanktmartinstag Tradition through Children's Song Entitled “Ich geh' mit meiner Laterne” - Rusdiani, Elita Putri; Usman, Rizman (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2024)
This research explores the background and moral values of the Sanktmartinstag tradition in Germany and its connection to the story of St. Martin through the analysis of song lyrics and visual imagery in the video clip of the song “Ich geh' mit meiner Laterne,” published on the YouTube channel “Sing mit mir-Kinderlieder.” The research adopts a qualitative descriptive approach, utilizing the Semiotic Method, as outlined by Roland Barthes, and ethnolinguistic studies to analyze the semiotic elements present in both the song and the visual representation. The findings reveal that the character of St. Martin embodies significant moral values, such as kindness, generosity, and compassion. These values, as depicted in the song and video, offer a meaningful foundation for character education and can be effectively integrated into educational settings to foster moral development. Through this research, it is concluded that the Sankt Martin tradition serves as a valuable tool for promoting ethical values in children's education.